"Do perceptions of EMU alter clarity of responsibility? A comparison of German and Greek electorates". (April 2021) - Lobo, Marina Costa; Pannico, Roberto
Abstract: The goal of this paper is to understand whether perceptions of supranationalisation of economic policy mitigate economic voting in the Eurozone. We focus on two countries with divergent performances in the Eurozone: Germany and Greece, and make use of a novel dataset, which contains all necessary items to test this hypothesis. Our comprehensive vote model shows that in both countries economic voting occurs. However, once we interact perceptions of EU responsibility with perceptions of economic performance, we obtain diverging results: in Germany, the weight of economic perceptions on vote increases when citizens assign a higher responsibility to the EU for the country's economic situation. This is the opposite of what the "blurring of responsibility" posits. On the contrary, Greek electors are in line with expectations of our main hypothesis. Moreover, in this country we also found support for the idea that only citizens with a high level of political sophistication are able to incorporate the distribution of responsibilities for the economic policy in their vote calculus. Our results suggest that the blurring of responsibility effect on the vote may not be systematic across the Eurozone.